Georgia Architectural and Historic Properties Survey of 206 and 208 Chandler St., Valdosta, Ga., December 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 206 and 208 Chandler St., Valdosta, Ga., December 1980. Two houses of square plan. Hipped, tin roof. Square posts supporting hipped porch. Exposed rafters. Shiplap siding. Set on brick piers. Double hung sash windows with 2/2 lights. Deteriorated condition. Date of Construction: App. 1910-1920. Significant as part of a potential National Register district which covers a 4 or 5 block area.
Georgia Architectural and Historic Properties Survey of 206 and 208 Chandler St., Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 79.6 MB (83,472,481 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)